The art of Eric Carle - Carle, Eric. (New York : Philomel Books, 1996)
Portrait of the children's author/illustrator, includes over sixty full-color illustrations from his books, examples of his student artwork, autobiographical information and photographs, and essays on his life and art by friends, critics, and colleagues.
"Books by Eric Carle": p. 120-123.
Includes index.
Wilson's Children
Booklist
Horn Book
Adult
Keywords: Carle, Eric -- Themes, motives; Picture books for children -- United States; Carle, Eric; Picture books for children